Framework nucleic acid programmed combinatorial delivery nanocarriers for parallel and multiplexed analysis. Issue 83 (1st October 2021) - Feng, Yinghui; Liu, Qi; Chen, Miao; Zhao, Xinyi; Wang, Lumin; Liu, Longfei; Chen, Xiaoqing
Abstract : An FNA-programmed strategy was proposed to develop nanocarriers to precisely and independently package multiple cargos in vitro and in vivo, thereby enabling multiplexed analysis, as well as favorable imaging and discrimination of different cells. Abstract : Herein we report a framework nucleic acid programmed strategy to develop nanocarriers to precisely and independently package multiple homo- and heterogeneous cargos in vitro and in vivo, thereby enabling multiplexed analysis of aptamer-ligand complexes to distinguish normal people and patients with prostate enlargement via simple serum tests, as well as favorable imaging and discrimination of MCF-7, PC-3 and A549 cancer cells and normal QSG-7701 cells.